An Academic Publisher’s Response to Plagiarism - Lewis, Bruce R.; Duchac, Jonathan E.; Douglas Beets, S. (2011)
Plagiarism strikes at the heart of academe, eroding the fundamental value of academic research. Recent evidence suggests that acts of plagiarism and awareness of these acts are on the rise in academia. To address this issue, a vein of research has emerged in recent years exploring plagiarism as an area of academic inquiry. In this new academic subject, case studies and analysis have been one of the most influential methodologies employed. Case studies provide a venue where acts of plagiarism can be discussed and analyzed in a constructive manner, and that is the primary purpose of this article. Unlike previous studies, however, we focus on the role of the publisher, a key player in dealing with acts of plagiarism, but one who has received little attention in the academic literature. Specifically, we examine how an academic publisher addressed allegations of plagiarism and how the publisher’s decision-making affected the outcome. We analyze the case by applying the guidelines from different frameworks and ethical theory and develop recommendations from the lessons evidenced, the second main objective of our article. This analysis advances the dialog on academic plagiarism by exploring the role of the publisher from a deontological perspective of ethical absolutism.
Keywords: codes of ethics; codes of conduct; publisher responsibilities; Plagiarism